2018
DOI: 10.1186/s12884-018-1890-2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers associated with care-seeking for institutional delivery among rural women in three provinces in Afghanistan

Abstract: BackgroundIn the past fifteen years, Afghanistan has made substantial progress in extending primary health care. However, coverage of essential health interventions proven to improve maternal and neonatal health outcomes, particularly skilled birth attendance, remains unacceptably low. This is especially true for those in the poorest quintile of the population. This cross-sectional quantitative and qualitative study assessed barriers associated with care-seeking for institutional delivery among rural Afghan wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 16 publications
5
33
0
Order By: Relevance
“…Mortality was higher among those treated with the individualized regimen, which is probably explained by the much higher frequency of baseline fluoroquinolone resistance in this cohort and concurrent co-morbidities. Indeed, initial fluoroquinolone resistance was a strong predictor of having an unfavorable outcome, which is coherent with other studies [ 10 , 21 , 26 30 ]. After adjusting for initial fluoroquinolone resistance, severity of disease on chest radiography, and other confounders, the choice of regimen was not correlated with having an unfavorable outcome.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mortality was higher among those treated with the individualized regimen, which is probably explained by the much higher frequency of baseline fluoroquinolone resistance in this cohort and concurrent co-morbidities. Indeed, initial fluoroquinolone resistance was a strong predictor of having an unfavorable outcome, which is coherent with other studies [ 10 , 21 , 26 30 ]. After adjusting for initial fluoroquinolone resistance, severity of disease on chest radiography, and other confounders, the choice of regimen was not correlated with having an unfavorable outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, one fifth of patients was diagnosed through systematic and repetitive screening among household contacts. Such approach is particularly important in contexts with a high TB burden among children and women, especially when cultural and gender barriers result in diagnostic delay [29,30]. Among 112 patients on treatment, 16 (14.3%) were children (< 15 years old).…”
Section: Plos Onementioning
confidence: 99%
“…The scenario worsens with limited number of health care professionals work in remote and rural areas, which is particularly applicable for countries such as Afghanistan, Bangladesh, India and Pakistan [78][79][80]. These add to the extra travel cost to access SBA services, which again is cheaper through home delivery by a TBA [81,82]. These were also supported by the findings obtained in the current study, as women with highest level of education were three times more likely to access modern delivery cares compared to women with no education, which also indicated that primary or basic level of education might not be enough for achieving the target of SDG 3.1.…”
Section: Plos Onementioning
confidence: 99%
“…No CCT studies also appear to have been conducted in conflict affected areas, though one study in Afghanistan has assessed feasibility [8]. We recently reported that barriers to MCH use in Afghanistan are similar to other Asian countries but lack of decision making ‘power’ of women in the family and the presence of anti-government elements in small villages are also important determinants [9, 10]. Families in conflict affected countries such as Afghanistan are likely to require additional assistance to enable them to use financial incentives.…”
Section: Introductionmentioning
confidence: 99%